Analisis Kualitas Website Sekato Jambi Menggunakan Metode Webqual 4.0 - Fernanda, M. Ridho; Sunoto, Akwan; Hendrawan (LPPM STIKOM Dinamika Bangsa, 2024)
Abstract− An online news portal is a website page that provides information about an event that has occurred. The information conveyed is not much different from the information in print media, only on the internet media or also known as online media. One of the media companies that applies an online basis in disseminating its news media is Sekato Jambi. The news presented by the Sekato Jambi website includes actual news containing local news such as economics, business, law, crime, sports, politics and government. The aim of this research is to evaluate the quality of the Sekato Jambi website using four characteristics of the Webqual 4.0 method, namely usability, information quality, interaction quality and user satisfaction. The author used Google Form to distribute online questionnaires to collect data for this research and succeeded in collecting a total of 360 respondents who had visited the Sekato Jambi website.